Phytoplankton size-fractionated chlorophyll-a off Baja California during winter, spring, and summer 2008 - Martínez-Almeida, Víctor M.; Gaxiola-Castro, Gilberto; Durazo, Reginaldo; Lara-Lara, J. Rubén (HIDROBIOLÓGICA, 2017)
Spatial and temporal size-fractionated phytoplankton chlorophyll-a (Chl-a) variability as pico-nanoplankton (PN, 0.4- 8.0 µm) and nano-microplankton (NM, >8.0 µm) off Baja California is shown. Chl-a samples from the upper 200 m were obtained from nearshore, offshore, and intermediate locations during winter, spring, and summer 2008. PN-Chl-a contribution to phytoplankton biomass was 4 times higher than NM fraction. Chl-a PN/NM ratio increased toward offshore, while total Chl-a (PN + NM) decreased. Seasonally, offshore phytoplankton cells abundance had a comparable contribution for both size-fractions, without an apparent change by the integrated water-column total Chl-a (60 mg m?2). Vertical Chl-a profiles were similar for winter and summer seasons. The highest Chl-a concentration and phytoplankton-cells abundance arose in spring, predominantly for NM at nearshore locations, reaching from 2.7-fold (nearshore: middle) to 4.2-fold (middle: offshore) ratios. Phytoplankton Chl-a increased from winter to spring (5.4 times), with maximum contribution of NM (6.6 times) at nearshore zones. Water-column integrated phytoplankton abundance was 5-fold higher in spring than winter, and 2-fold over summer. Using optical microscopy, dinoflagellate cells were the most abundant and variable phytoplankton recognizable group at intermediate zone. Smaller phytoplankton cells sustained approximately continuous biomass off Baja California. The spatial and temporal phytoplankton biomass variability was mainly influenced by an increase of larger cells as result of spring coastal upwelling events.